The Neglected Traditional Enset (Ensete ventricosum) Crop Landraces for the Sustainable Livelihood of the Local People in Southern Ethiopia - Newarinesh Feleke; Wondimagegnehu Tekalign (International Journal of Food Science)
Enset (Ensete ventricosum, Musaceae) is a neglected traditional multipurpose crop plant critical for Ethiopian food security. It has drawn a lot of attention in the last few years. This study was undertaken on the morphological diversity among the enset landraces and their cultural use for the livelihood of the people in Southern Ethiopia. The study was administered in four purposively selected kebeles of the Mareka District. A total of 145 individuals were interviewed using semistructured interviews, and field observation has also occurred. The descriptors for enset developed by the International Board for Plant Genetic Resources were used to measure the morphological features. This study found twenty-two enset landraces. Landraces were categorized into five groups based on their morphological trait variability. The highest mean was in cluster five, while the lowest was in cluster three. The highest landrace diversity was found in Ocha (n=2.28) and the lowest in Guta (n=2.17). This study confirmed that the study area has a diverse range of ecosystems. However, a reduction in production and the loss of some landraces were observed. As a result, the protection and preservation of enset landraces must be a priority for all responsible entities.